"THE BEST DOCTOR FOR MY SOUL": how the parrhesiastic relationship between princess elisabeth of bohemia and rené descartes belies descartes's dualism and foucault's neoliberalism. Issue 5 (3rd September 2018) - Tierney, Thomas F.
Abstract: This article contributes to the revaluation of the much-maligned figure of René Descartes, by interpreting his relationship with Princess Elisabeth of Bohemia through Michel Foucault's late work on the "care of the self" and parrēsia . In addition to challenging Descartes's reputation for endorsing a rigid mind–body dualism, the essay also challenges those who interpret Foucault's work on ancient techniques of the self as supportive of neoliberalism. On the contrary, this essay argues that Foucault's turn to ancient sources was offered as a critique of neoliberalism, and uses the mutually beneficial relationship between Descartes and Elisabeth as a counter-example to neoliberalism's individualistic, entrepreneurial conception of the self. The essay concludes with a brief examination of Elisabeth's exercise of power in a manner that both Descartes and Foucault could endorse, and which can serve as a challenge to the xenophobic, nationalistic leadership that has arisen of late.